Influence of MCPA on Fusarium oxysporum root rot and red clover growth under controlled greenhouse conditions - Ceballos, Ricardo; Palma, Graciela; Perich, Fernando; Pardo, Fernando; Quiroz, Andrés (Phytoprotection, 2006)
AbstractRoot rot caused by Fusarium oxysporum is a disease that reduces red clover persistence. Agronomical management of red clover includes MCPA application, and there is no information regarding the effects of this herbicide on the disease. MCPA was evaluated for its effects on F. oxysporum root rot and red clover (Trifolium pratense) growth in a greenhouse experiment. Additionally, in vitro mycelial growth and conidial germination of F. oxysporum were studied. For shoot dry weight and crown diameter of seedlings, the interaction of herbicide and inoculum was significant at 30 d. The herbicide–inoculum treatment reduced shoot dry weight by 20% at 1X rate and by 24% at 2X rate, and crown diameter was reduced by 10% at the high rate. The MCPA treatment caused a 40% reduction of root dry weight by the end of the experiment. Application of MCPA caused fusarium root rot to increase in severity on red clover seedlings and caused phytotoxicity at the high rate. Interaction with the other growth parameters was not significant, indicating that the effects of herbicide and inoculum were independent. Conidial germination and mycelial growth in vitro were reduced by MCPA. Results suggest that red clover growth could be negatively affected by F. oxysporum after MCPA application and that root rot severity increases at high rates of MCPA.